White matter microstructure abnormalities in thalassemia patients using TBSS analysis based on DTI - Yang, Mingrui; Chen, Guowei; Luo, Chaotian; Tang, Cheng; Peng, Fei; Kong, Rong; Peng, Peng (Scientific reports, 2025)
Thalassemia is a hereditary hemoglobinopathy characterized by severe anemia and iron overload, which may affect brain microstructure. This study aims to investigate changes in the white matter (WM) microstructure of patients with β-thalassemia using diffusion tensor imaging (DTI) and tract-based spatial statistics (TBSS) analysis. The study included 40 patients with β-thalassemia (aged 18–45 years, mean age 30.65 years) and 40 healthy controls (aged 18–45 years, mean age 30.13 years). All participants underwent 3.0 T MRI scans. DTI data were processed using the FSL software package, focusing on the assessment of four indices: fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), and axial diffusivity (AD). The receiver operating characteristic (ROC) curve area under the curve (AUC) was calculated for these indices to highlight the potential value of white matter regions in distinguishing between patient and control group. Compared to the control group, patients with β-thalassemia showed decreased FA and increased MD and RD in multiple white matter tracts. ROC curve analysis showed high AUC values for FA, MD, and RD (0.868, 0.854, and 0.847, respectively). The results suggest that patients with β-thalassemia may have widespread abnormalities in the white matter microstructure.